Gradual Constitutional Change and Federal Dynamics – German Federalism Reform in Historical Perspective. Issue 5 (19th October 2016) - Benz, Arthur
ABSTRACT: In order to understand reform in German federalism, this article applies the framework of "dynamic institutionalism". It explains change as a result of a particular pattern of constitutional policy emerging in a sequential evolution of institutions and responding to changing state–society relations. Historical legacies found expression in negotiations predominated by bargaining among governments, guided by legalist approaches of lawyers and court decisions and influenced by specialists in public administration. In this context, societal change affected the agenda but had limited impact on processes and outcomes. In consequence, the reform ended with many detailed constitutional amendments not amounting to substantial change. In a comparative perspective, German federalism may have its strengths, but its reform should not be regarded as a role model for other federations. Instead, it exemplifies the problematic consequences of a constitutional policy not sufficiently separated from normal intergovernmental policy-making and strongly embedded in a self-enforcing evolution of institutions.